2022
DOI: 10.3390/ijerph19073936
|View full text |Cite
|
Sign up to set email alerts
|

Securing Smokefree Laws Covering Casinos and Bars in Louisiana via Messaging, Continuous Campaigning and Health Coalitions

Abstract: In this paper, we examine efforts by health organizations seeking comprehensive smokefree ordinances over Louisiana casinos and bars between 2010 and 2020 to determine best practices for increasing coverage. Bars and casinos remain less protected from secondhand smoke compared to other workplaces in the United States. Casino behavior is compared to the Policy Dystopia Model (PDM), a tobacco industry strategy framework. We performed a historical case study using snowball searches for news on the Access World Ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Smokefree legislation and policies have increased globally [1][2][3][4]. In most EU countries, smokefree laws have been implemented in public buildings and in private businesses [3,5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Smokefree legislation and policies have increased globally [1][2][3][4]. In most EU countries, smokefree laws have been implemented in public buildings and in private businesses [3,5,6].…”
Section: Introductionmentioning
confidence: 99%
“…They found that the proposed IAQ certification complies with international standards and has continuous monitoring and information disclosure methods. In another paper, Wakefield and Glantz [2] examined efforts by health organizations seeking comprehensive smoke-free ordinances over Louisiana casinos and bars.…”
mentioning
confidence: 99%